Persistent and recurrent stress urinary incontinence following mid-urethral tape surgery in women: a UK perspective. (January 2013) - Mohammed, Aza; Maguire, Turlough; Biers, Suzanne; Terry, Tim R
Stress urinary incontinence is a common health problem that affects a large proportion of women in Britain. It poses physical and psychological implications for the affected women and is a frequent indication for referral to tertiary urology centres. Midurethral tape surgery (MUTS) has established itself as the standard first-line surgical treatment as a result of its low morbidity, short hospital stay and high long-term success. Failure of the initial surgery can present as persistent or recurrent symptoms. This is a major challenge to the treating urologists as a result of the complicated nature of the condition and the lack of strong evidence supporting individual treatment modalities. In this article we discuss the factors associated with MUTS failure and the surgical options for its treatment.